No Man's Time. - Bernard, Christian; Troncy, Eric (Nice : Villa Arson, 1991)
Agerbeek, Richard ; Bond, Henry ; Gillick, Liam ; BP ; Bulloch, Angela ; Fleury, Sylvie ; Gonzalez-Foerster, Dominique ; Gonzalez-Torres, Felix ; Ismora, Manuel ; Ménard, Pierre ; Joseph, Pierre ; Kilimnik, Karen ; Kongrosian, Richard ; Morgana, Aimee ; Muyle, Johan ; Pruitt,Early ; Parreno, Philippe ; Pettibon, Raymond ; Un mauvais artiste ; Ruppersberg, Allen ; Shaw, Jim ; van der Stokker, Lily ; Kippenberger, Martin ; Veilhan, Xavier
No Man's Time, Villa Arson, Nice, 6 juillet - 30 septembre 1991
boek